PREVENTIVE CARE IN FAMILY MEDICINE: AN EVIDENCE-BASED REVIEW OF CURRENT GUIDELINES AND INNOVATIONS - Dr. Raya Khudhair Mohsin (Web of Journals Publishing, 2025)
Chronic preventable diseases account for 74% of global mortality, necessitating pressing optimization of preventive care strategies. This systematic evaluate synthesizes evidence from 127 studies (2013–2023) and pointers from USPSTF, NICE, and WHO to evaluate the efficacy of preventive interventions and emerging improvements. Findings monitor that guideline-concordant screenings (e.G., colonoscopy, HbA1c trying out) reduce disease-unique mortality by forty–60%, yet adherence rates vary widely, with rural and socioeconomically deprived populations experiencing 30–35% decrease carrier utilization. Innovations together with AI-driven selection support systems progressed preventive provider transport by using 22% in trials, although algorithmic biases underpredicted risks in ethnic minorities through 18%. Organizational fashions like included prevention clinics decreased hospitalizations by means of 19%, whilst telemedicine multiplied rural get entry to to high blood pressure screenings by means of 35%. However, sustainability challenges persist, particularly in low-aid settings. The evaluation identifies three vital gaps: inconsistent guiding principal harmonization, underfunded prevention infrastructure, and insufficient fairness-targeted innovation. Recommendations include scaling virtual fitness gear with bias audits, reallocating 15% of country wide fitness budgets to prevention, and setting up primary care training hubs for emerging technology. These strategies, aligned with WHO’s 2030 prevention goals, provide a roadmap for lowering preventable morbidity thru proof-based totally, equitable interventions.
Keywords: Preventive care - Family medicine - Evidence-based guidelines - Digital health innovations - Health equity.